A 3rd order narrowband bandpass filter based on shorted coupled-lines resonator / Mohd Nasiruddin Hushim ...[et al.] - Hushim, Mohd Nasiruddin; Ab Wahab, Norfishah; Abdul Khalid, Muhammad Farid; Adzhar, Mohd Khairil (Universiti Teknologi MARA, 2019)
This paper presents a class of side-coupled shorted coupled-lines resonator topology for narrowband bandpass filter applications. The base topology is constructed by interconnecting two shorted quarter-wavelength coupled-line sections to exhibit a single resonance bandpass filter response. The degree of order of the resonator can be increased by inter-connecting additional shorted quarter-wavelength coupled-line sections to the base cell. Based on this concept, a 3rd order bandpass filter is constructed by inter-connecting two new shorted quarter wavelength coupled-line sections into the base cell. The advantage of this new 3rd order filter arrangement is that, the affect of inter-connecting the shorted coupled-line sections had caused cross-coupling between the adjacent coupled-lines to produce a transmission zero at the lower passband. For compactness, all the coupled-lines of the 3rd order filter are meandered, resulting to 40% of size reduction. To prove the concept, the 3 rd order bandpass filter was simulated using full wave electromagnetic simulation tool. The filter was designed at 1 GHz on microstrip substrate type Roger RO3210. A prototype of the 3rd order bandpass filter was fabricated and the results are compared and are found agreable